A web for Supreme Judicial Institute Library in Yemen - Ayu, Media Anugerah; Al-Ghashm, Abdulraoof Mohammed (IIUM Press, 2011)
This chapter discusses about the development of a website for Supreme Judicial Institute Library in Yemen. This project intended to serve (S1I)Library administration, staff (lecturers, researchers, and management), and students. The objectives of this project is to develop and build a website for the SJI library in Yemen to provide Automated searching, booking, and checking the statues of the book by remote users anywhere and anytime,Automated book management to add, update, save, borrow and delete books and journals and their information, and Automated users and staff management to add, update, save and delete their information accordingly. The system is developed using Macromedia Dreamweaver, PHP, and MySQL.